One-Dimensional Coiiand Niiihelical Coordination Polymers Exhibiting Zero-Field Splitting - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2023)
Two new coordination polymers {[MII(HL)(EtOH)2](ClO4)}n, where MII= Co (1) and Ni (2), were synthesized using a Schiff base ligand H2L = 2-{[(E)-1H-imidazol-4-ylmethylidene}amino]benzoic acid. Compounds 1 and 2 are isostructural, presenting a one-dimensional helical chain arrangement. Each metal center has a distorted octahedral geometry bridged by a syn-anti carboxylate group. The fitting of the magnetic susceptibility data in the 1.8-300 K range shows weak intrachain antiferromagnetic interaction for 1 and weak ferromagnetic interaction for 2, with the presence of zero-field splitting (zfs) phenomenon in both compounds. Theoretical calculations confirm the weak intrachain coupling in both compounds, but with a zfs phenomenon dominant at lower temperatures. A positive value for the zfs is also obtained, with a major spin-orbit coupling component. © 2022 American Chemical Society